The organic metaphor in twentieth-century Lusophone urban geography: cities and their history in the work of Aroldo de Azevedo and Orlando Ribeiro - Paiva, Daniel (2020)
This article investigates the use of organic metaphors in Lusophone urban geography of the Vidalian paradigm. There is presently a growing body of literature on the use of metaphors in urban studies in the Anglophone academy, yet the use of metaphors in urban studies in other languages seems to be an unexplored matter. To tackle this issue, we examine the work of Aroldo de Azevedo (1910e1974), a Brazilian geographer at the University of Sao Paulo, and Orlando Ribeiro (1911 ~ e1997), a Portuguese geographer at the University of Lisbon. The choice of these authors is based on the high visibility of their work in both Brazilian and Portuguese geography and urban studies, as well as the long-standing dialogue between them. We will show that Aroldo de Azevedo and Orlando Ribeiro mobilised organic metaphors to explain the history and form of the cities founded by the Portuguese, establishing a common language for the Lusophone geography community. We will also discuss how they used organic metaphors to criticise the logics of large scale urban planning, and, more importantly, the perspectives and techniques of spatial science. In a broader sense, this study also shows that considering the use of metaphors provides a novel way of examining scientific controversies beyond ideas of the succession of paradigms.